KORELASI TEOLOGIS ANTARA AGONIZOMAI DENGAN HALAS DAN PHOS: Komitmen Kristen untuk Menjadi Saksi Kristus - Stenly R. Paparang (Sekolah Tinggi Teologi Moriah, 2019)
As Witnesses of Christ, striving for the Gospel and experiencing the suffering are consequence of faith. Struggle to against all sin, corruption, and the darkness of the world is manifestation from disciple’s identity as salt and light of the world. In that line, the struggle of (??????????) Christians also called as manifestation of personal identity that attached to ‘salt’ (????) and ‘light’ (???) the world. The aims from this article to explain the theological correlation between ?????????? with ???? and ???. The correlation is manifested in two contexts of responsibility: first, the responsibility of faith in preaching the Gospel, preserving the world from corruption because of sin and human wickedness, as the manifestation from identity of ???? ??? ???; and second, the responsibility as follower of Jesus Christ in radiase the light of His love as a manifestation from identity of ??? ??? ??????. A descriptive-biblical approach is used to explain the meaning of the reference texts and explain the theological correlation between ?????????? and ???? and ???. Sebagai saksi Kristus, berjuang demi Injil dan mengalami penderitaan adalah sebuah konsekuensi iman. Perjuangan melawan dosa, kebusukan, dan kegelapan dunia adalah wujud dari identitas para murid sebagai garam dunia dan terang dunia. Sejalan dengan itu, perjuangan (??????????) orang Kristen juga merupakan wujud dari identitas personal yang melekat padanya yakni ‘garam’ (????) dan ‘terang’ (???) dunia. Artikel ini bertujuan untuk menjelaskan korelasi teologis antara ?????????? dengan ???? dan ???. Korelasi tersebut terwujud dalam dua konteks tanggung jawab: pertama, tanggung jawab iman dalam memberitakan Injil, mengawetkan dunia dari pembusukan karena dosa dan kejahatan manusia, sebagai perwujudan dari identitas ???? ??? ???; dan kedua, tanggung jawab sebagai pengikut Yesus Kristus dalam memancarkan terang kasih-Nya sebagai perwujudan dari identitas ??? ??? ??????. Pendekatan deskriptif-biblika digunakan untuk menjelaskan makna dari teks-teks rujukan dan menjelaskan korelasi teologis antara ?????????? dengan ???? dan ???.